Optical coherence tomography angiography and the visual field in hypertensive and normotensive glaucoma - Zakova, Marketa; Lestak, Jan; Fus, Martin; Maresova, Klara (Biomedical papers, 2021)
Background. Hypertensive glaucoma (HTG) causes damage to the retinal ganglion cells and eventually to the entire visual pathway due to high intraocular pressure (IOP). However, increased IOP will also affect the vessel density (VD) of the posterior pole of the eye and the related retinal ganglion nerve fibres (RNFL). In normotensive glaucoma (NTG), the retinal ganglion cells are relatively intact. The pathology is at the level of ganglion fibres. The unanswered question is what has altered ganglion cell fibres at the level of the retina and optic nerve head in NTG? Aim. The aim of this study was to determine whether there is a correlation between the retinal nerve fibre layer (RNFL) and vessel density (VD) at the same altitudinal half of the retina and the sum of sensitivities of the contralateral half of the visual field of the same eye in hypertensive and normotensive glaucoma (NTG). Methods. Our group included 20 patients with HTG and 20 patients with NTG. The Pearson's correlation coefficient r was used for evaluation of the relationship of the peripapillary RNFL and VD, visual field (using the fast threshold glaucoma program) as the sum of sensitivities in apostilbs (asb) to the extent of 0-22 degrees. The results of sensitivity were compared with the RNFL and VD of the contralateral altitudinal half of the retina in the same eye. Results. In the HTG group there was a moderate relationship between RNFL and VD (both hemifields), but no relationship between RNFL and VF. VD SH and VF IH showed weak correlation and VD IH and VF SH showed no correlation. In patients with NTG, we found a strong correlation between RNFL and VD (both hemifields), between VD SH and VF IH a moderate correlation, between VD IH and VF SH also a moderate correlation and a weak correlation between RNFL and VF. Conclusion. By comparing the RNFL and VD at the same altitudinal halves of the retina, we found a moderate correlation in HTG and a strong correlation in NTG. We found no or a weak correlation between VD and VF in HTG. In NTG the relationship between VD and VF showed a strong correlation. These findings reveal the differences in the diagnostic groups.
Keywords: retinal nerve fibre layer; optical coherence tomography angiography; vessel density; visual field; hypertensive glaucoma; normotensive glaucoma